Changing neo-corporatist institutions? Examining the relationship between government and civil society organizations in Belgium. Issue 8 (3rd August 2021) - Pauly, Raf; Verschuere, Bram; De Rynck, Filip; Voets, Joris
ABSTRACT: Neo-corporatist relations consist of a stabilized institutional exchange between government, civil society and other social spheres. Current research suggests a destabilization of this relationship by ongoing governance developments, especially through the competitive pressures of NPM-style reforms. This article presents survey research of 339 civil society organizations in the neo-corporatist context of Belgium. We find little evidence of increased marketization, contrary to existing literature. In fact, our data suggest that neo-corporatist relations, at least in terms of formalized exchange, are rather stable, although the nature of specific institutions (such as the nature of public funding) appears to shift.